EVALUATION OF INTERNAL VISITORS MANAGEMENT CONTROLLING ENVIRONMENTAL IMPACT AT CAMPSITE RANU KUMBOLO TNBTS - Tri Octavia Lestari; Hery Sigit Cahyadi; Rachmat Syam (Politeknik Pariwisata NHI Bandung, 2022)
Camping activity is one of the outdoor activities that are considered to have the biggest role in environmental damage. On the other hand, the impact of environmental degradation can be substantially minimized by managing visitor behavior. The formulation of a visitor management framework as a strategy to achieve a sustainable state needs to pay attention to 3 basic elements that are interrelated, namely the formulation of indicators and standards according to management objectives, implementation of a monitoring system, and implementation of strategies to maintain conditions according to predetermined standards. A documentation study based on the standard operating procedure of hiking activity at Ranu Kumbolo Campsite was done to evaluate the accuracy of the visitor management strategy carried out by the Bromo Tengger Semeru National Park as the area manager in addressing the environmental impact problems that occurred.